Incidences of Birth Abnormalities, Congenital Defects and their Association with Consanguineous Marriages in Rajshahi: A Case Study - Islam, M Saiful; Ahmed, Sharmin (Journal of Bio-Science, 2011)
Context: It has long been claimed that consanguineous marriages are deleterious to human well beings, but their association with incidences of birth abnormalities and congenital defects has not been well studied in our societies. Objectives: To investigate frequencies of common birth abnormalities and congenital defects in children from congenital marriages in Rajshahi Metropolis areas. Materials and Methods: A total of 150 clinical patients were chosen at random from 10 hospitals and clinics for recording their birth related abnormalities, whereas 281 children from 100 consanguineous couples from 17 Wards were included in the study for examining their congenital defects. All the patients, children and their parents were interviewed separately for recording the case histories. Results: Frequencies of miscarriages (0.65), stillbirths (0.38), postnatal deaths (0.30), and preterm deliveries (0.50) each in consanguineous cases differed significantly from that in non-consanguineous cases (P<0.001). In addition, significantly shortened gestational ages (34.37±4.08 wks) and lower live birth weights (3.20±0.72 kg) prevailed in the children from consanguineous marriages (P<0.001). Frequencies of six congenital defects in 76 children (30 females: 46 males) viz., deaf-mutism (0.70), cerebral palsy (0.12), mental retardation (0.11), blindness (0.04), syndactyly (0.02) and deaf-mutism coupled with mental retardation (0.01), were recorded from 100 consanguineous couples who had a total of 281 children. Conclusion: Demerits of the prevailing tradition of marrying close relatives in our society are obvious from the present results. Moreover, association between consanguinity and various birth and congenital malformations was statistically significant compared to the non-consanguineous cases. Key words: Birth abnormalities; congenital defects; consanguineous marriages DOI: 10.3329/jbs.v17i0.7115 J. bio-sci. 17: 107-112, 2009